Fishermen and Consumptive Behavior: An Ethnographic Study of the Muncar Banyuwangi District Community - Fauzi, Niken Eriana Azzahra; Kumalasari, Anis; Oktaferly, Fayza Jasmine (Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The fishing community in Kedungrejo Village, Muncar District, is deeply intertwined with a consumerist lifestyle. Every social group, from the fisherman owners, laborers, to factory workers, creates its own distinct reflection of this lifestyle. This study aims to depict the lifestyle or way of life formed within the fishing community. Using a qualitative approach, the research explains the phenomenon descriptively. The ethnographic study focuses on a group of fishing communities, providing a perspective from the fishermen as the primary informants. This allows for an understanding of consumerism patterns connected to the culture and traditions of the fishing community, along with the socioeconomic status linked to the impact of the fishermen’s catch. Through data collection methods such as observation, interviews, and documentation, the study finds that the fishing community in Kedungrejo exhibits a consumptive lifestyle, as evidenced by their habit of purchasing luxury goods to maintain their social status in the surrounding environment. Additionally, their purchases are driven by personal desires. The fisherman owners, perceived to be in the upper social class, attempt to highlight their identity as wealthy and powerful. This research applies Jean Baudrillard’s theory of consumerism, which assumes that individual identity is collectively shaped by commercial interests rather than utility. Just as societies represent needs, consumerism leads individuals or groups to believe in the symbolic power of possessing specific goods.